2020
DOI: 10.1002/pc.25507
|View full text |Cite
|
Sign up to set email alerts
|

Result of vascular tube design on the curative and mechanical performance of modified carbon fibers/hybrid resin self‐healing composites

Abstract: The current study focuses on the design of healing carriers (vascular tube) for enhancing the healing behavior and mechanical properties of healing composites by reinforcing hybrid resin (vinyl ester:epoxy [80:20]) with phenol‐treated carbon fibers and inserting macrovascular tubes by using the vacuum‐assisted resin transfer mold (VARTM) process. Epoxy, vinyl ester (VE), and hybrid resin (HR) were incorporated in the vascular tubes as healing agents and introduced in three designs. The effect of phenol treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Williams et al 62 were the first to report the use of hollow glass fibers as a carrier for repairing CFRP, which could effectively repair matrix cracks and achieve repeat repairs. Kumar et al 63 treated carbon fibers with phenol and layered them in a certain way with glass tubes filled by epoxy and vinyl ester healing agents. The results showed that the phenol‐treated carbon fibers had a stronger interaction with polymer matrix than original fibers.…”
Section: Extrinsic Self‐healing Compositesmentioning
confidence: 99%
“…Williams et al 62 were the first to report the use of hollow glass fibers as a carrier for repairing CFRP, which could effectively repair matrix cracks and achieve repeat repairs. Kumar et al 63 treated carbon fibers with phenol and layered them in a certain way with glass tubes filled by epoxy and vinyl ester healing agents. The results showed that the phenol‐treated carbon fibers had a stronger interaction with polymer matrix than original fibers.…”
Section: Extrinsic Self‐healing Compositesmentioning
confidence: 99%
“…In extrinsic systems, the self‐healing ability is activated autonomously, 17 while in intrinsic systems, the self‐healing process must be triggered through the use of external stimuli, such as temperature, voltage, and magnetic field 18 . In extrinsic self‐healing composites, the healing agent is usually contained in capsules 1920 , 21 vascular networks, 22 or nanoparticles, and has to be incorporated into the materials during the production of the composites 23 . When cracks occur within the material as a result of a damage event, the capsule or vascular network breakage allows the release of the healing agent into the damaged area.…”
Section: Introductionmentioning
confidence: 99%
“…and introduced into the host matrix material so that the healing agents can be released to achieve autonomous repair when the material is exposed to external damage. [19][20][21][22] LVI is a major source of damage for composite materials in real-world applications. In this regard, previous researchers have conducted a series of self-repair performance studies on composites for impact damage based on the above two systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the resin matrix based on the Diels–Alder reaction has garnered significant attention due to its reversible repair characteristics, which allow the composite material to undergo multiple repairs 16–18 ; (b) the extrinsic type, in which self‐healing agents are encapsulated in micro‐memories (microcapsules, hollow fibers, and microvessels, etc.) and introduced into the host matrix material so that the healing agents can be released to achieve autonomous repair when the material is exposed to external damage 19–22 …”
Section: Introductionmentioning
confidence: 99%